Finite element analysis of mechanical behavior of human dysplastic hip joints: a systematic review. Issue 4 (April 2017) - Vafaeian, B.; Zonoobi, D.; Mabee, M.; Hareendranathan, A.R.; El-Rich, M.; Adeeb, S.; Jaremko, J.L.
Summary: Developmental dysplasia of the hip (DDH) is a common condition predisposing to osteoarthritis (OA). Especially since DDH is best identified and treated in infancy before bones ossify, there is surprisingly a near-complete absence of literature examining mechanical behavior of infant dysplastic hips. We sought to identify current practice in finite element modeling (FEM) of DDH, to inform future modeling of infant dysplastic hips. We performed multi-database systematic review using PRISMA criteria. Abstracts ( n  = 126) fulfilling inclusion criteria were screened for methodological quality, and results were analyzed and summarized for eligible articles ( n  = 12). The majority of the studies modeled human adult dysplastic hips. Two studies focused on etiology of DDH through simulating mechanobiological growth of prenatal hips; we found no FEM-based studies in infants or children. Finite element models used either patient-specific geometry or idealized average geometry. Diversities in choice of material properties, boundary conditions, and loading scenarios were found in the finite-element models. FEM of adult dysplastic hips demonstrated generally smaller cartilage contact area in dysplastic hips than in normal joints. Contact pressure (CP) may be higher or lower in dysplastic hips depending on joint geometry and mechanical contribution of labrum (Lb). FEM of mechanobiological growth of prenatal hip joints revealed evidence for effects of the joint mechanical environment on formation of coxa valga, asymmetrically shallow acetabulum and malformed femoral head associated with DDH. Future modeling informed by the results of this review may yield valuable insights into optimal treatment of DDH, and into how and why OA develops early in DDH.